Ask and They Will Listen: Economic Justice, Political Agency, and a Right to Health in Uganda. Issue 2 (17th November 2022) - Boyd, Lydia
Abstract: Over the last two decades, courts have emerged as increasingly important fields of struggle in the fight for maternal health rights. While the success of litigation has been celebrated as a sign of the strength of rights‐based platforms as advocacy tools, critics of this approach have highlighted how these cases may do little to permanently address the systemic inequality that drives poor maternal health outcomes. Such critiques highlight persistent questions regarding the efficacy of human rights to address issues of economic inequality. This article explores these tensions by examining a legal case and associated advocacy for health rights in Uganda. By drawing on Ugandan political norms that emphasize the ways rights are collective and shaped by mutual obligations, activists have helped to draw the state back into debates over resource allocation even as neoliberal reforms have worked to sideline state investment in healthcare in the region. This article explores how African cultural frameworks for political advocacy may be effective in positioning the problem of economic inequality as a human rights issue in ways Western frameworks have not been.